ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK MALUKU MALUT PADA MASA PANDEMI COVID-19 - Roberto Akyuwen; Marthin Nanere; Suwandi Suwandi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
The corona virus diseases 2019 (Covid-19) has spread widely in Indonesia since the beginning of 2020. Until recently, this pandemic has gradually disturbed the whole social and economic sectors including banking industry. Bankers are facing various challenges and uncertainties in sustaining their businesses and simultaneously anticipating the better situation in the future. This research is aimed to identify the impact of capital adequacy, loan distribution, and efficiency on the profitability of Bank Maluku Malut in the Covid-19 pandemic period. This bank is basically categorized as a commercial bank. However, it also being recognized as a regional development bank. In total, there were 26 regional development banks in Indonesia. All financial data of Bank Maluku Malut which are required for analysis in this research are gathered from the Indonesia Financial Services Authority (OJK). These data were analyzed using a multiple linear regression model. It was found that the loan distribution has a significant and positive influence on the profitability. Meanwhile, the efficiency has a significant but negative impact on the profitability. The other finding is that the capital adequacy has no impact on the bank’s profitability.